The Similarities and Differences of the Translatological Means of Representing the Concept of "Desire" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Several isomorphic and allomorphic features of the verbal and nonverbal mechanisms that implement the idea of "purpose" in various systematic languages are the main topic of this essay. Examples from a fictional work are used to analyze each of them.